Evaluation of the Antidepressant Effect of Propolis in Chronic Unpredictable Mild Stress-induced Depression Model in Rats - Ali TAŞKIRAN; Fadime CANBOLAT; Sena Nur YÜCELLİ; Burcu ÇEVRELİ (Namık Kemal Tıp Dergisi, 2023)

(untitled)
Aim:In this study, the antidepressant effect of propolis was investigated in a model of chronic unpredictable depression in rats.Materials and Methods:Wistar-Albino male rats were used in the study and were divided into four groups as propolis, stress, stress+propolis, and control groups. Eight animals were assigned to each group. The experimental protocol was applied to the stress groups for 60 days, and the animals were exposed to different stressors. Propolis extract (100 mg/kg) was administered orally to propolis and stress+propolis groups throughout the experimental protocol. As a result of depression modeling, the Forced Swimming Test, Sucrose Preference Test, and Elevated Plus Maze Test were applied for behavioral evaluation. 24-hour urine samples were collected for quantification analysis of serotonin (5-HT) and its metabolite 5-hydroxy indole acetic acid (5-HIAA) in urine by liquid chromatography-tandem mass spectrometry (LC-MS/MS) method. The animals were sacrificed as a result of the experiment process. The results obtained from the study were analyzed using the Statistical Package for the Social Sciences.Results:It was seen that there was a statistical difference for behavioral tests between the groups (p<0.05). The administration of propolis to rats under stress has been shown to alter sugar consumption in rats (p<0.05). For Forced Swimming Test, there was a statistical difference between the stress group and the other groups. For 5-HT and 5-HIAA levels, there was no significant difference between the groups (p>0.05).Conclusion:The findings have shown that propolis extract may help to prevent depression, thanks to its antidepressant-like effects.